MENINGKATKAN HASIL BELAJAR SISWA MELALUI PENERAPAN MODEL PENEMUAN TERBIMBING PADA MATERI LARUTAN PENYANGGA BERBANTUAN MACROMEDIA FLASH KELAS XI IPA SMA MUHAMMADIYAH 1 BANJARMASIN - Iswan Setiadi (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2018)
Abstract. The research usedthe guided discovery model of the material buffer in class XI SMA Muhammadiyah 1 Banjarmasin. This study aimed to determine the increase about (1) the activities of teachers, (2) the activity of students, (3) learning outcomes, and (4) student response. The research design was classroom action research (PTK) where it conducted in cyclical. Each cycle is divided to planning, action, observation and reflection. Subjects numbered 21 people. The research instrument was a test and nontest. Data analysis used descriptive of quantitative and qualitative analysis. The results showed that (1) the activities of teachers in the first cycle with the percentage of 62,98% increased by 7,68% in the second cycle into 70,66%, (2) the activity of students in the first cycle with the percentage of 58.84% increased by 11,08% in the second cycle into 69,92%, (3) cognitive learning outcomes of students in the first cycle with a percentage of 42,86% increased by 33,33% in cycle II to 76,19%, the first cycle process skills of students with percentage 66,38% increase of 11.00% in cycle II to 77,38%, the results of the first cycle of learning psychomotor first meeting with a percentage of 66,40% increased by 11,20% in the second cycle to 77,60%, affective learning outcomes students in the first cycle with a percentage of 48,56% increased by 30,01% in the second cycle into 78,57%, and (4) the response of students in the learning process macromedia flash-assisted guided discovery showed positive results with the percentage of 80,95%.Keyword: guided discovery learning, learning outcomes, macromediaflash